(untitled) (Journal of Kathmandu Medical College, 2014)
Ectopic pregnancy is a life threatening condition and can present itself in diverse ways. This case reports a 23 years primigravida, admitted with history of amenorrhoea of ten weeks and right sided unruptured tubal pregnancy diagnosed on routine ultrasonography. On laparoscopy, there was an unruptured tubal pregnancy with gestational sac measuring around 6 × 5 cm. The foetus had crown rump length of 32 mm and foot length of 5 mm; both of which correspond probably to 10 to 11 weeks size. Segmental resection of the affected part of the fallopian tube was done laparoscopically. Rarely tubal pregnancy can remain asymptomatic and unruptured for longer duration of gestation than the usual scenario. The reported average duration of diagnosis of unruptured tubal pregnancy is of nine weeks and this case explores the possibility of removing an intact foetus at longer gestational age through laparoscopy. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 148-151 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9966 Uploaded date : 3/4/2014